ANALYSIS OF THE PROCESS STRATEGY IN CATFISH FARMING MITRA MAKMUR TULUNGAGUNG - Sari, Rafika Meilia (Manajemen Bisnis, 2015)
The research aims is to determine time process duration of catfish cultivation. Processing chart used to analyse time determination in cultivation process. Processing chart shows a series of activities, operating time cycle, value-added time, and non value-added activities. The result shows that to produce 1 pool of catfish need 80 days with 1.5 eficiency level. Catfish size was standardized in harvest time and the farmer earn some profits.